Occurrence of heavy metals in fish species, water and sediments of the Pasur River in Bangladesh along with assessments of ecological and human health risks - Evena Parvin Lipy; Md. Tazinur Rahman; Sadia Islam; Mohammad Raknuzzaman; Md. Monirul Islam; Samina Akhter; Dipa Islam; Mustafizur Rahman Naim; Mohammad Moniruzzaman; Anindita Biswas; Mahmuda Hakim; Chadni Lyzu (Discover Environment)
Abstract The present study was conducted to determine the extent of pollution of the Pasur River by HM, as well as the ecological and human health risks associated with the consumption of HM-contaminated fishes. For this purpose, the level of Pb, Cd, Cr, Cu, Ni, Mn, Zn and Co in water and Pb, Cd, Cr, Cu and Ni in sediment were evaluated. The mean concentrations of HMs in the water and sediment decreased in the order Pb > Cd > Ni > Cr > Zn > Co > Cu > Mn and Pb > Cr > Ni > Cu > Cd, respectively. Except for Pb and Cd in water, the HM concentrations were below the WHO standard of 0.01, 0.003, 0.05, 2.0, 0.07, and 0.05 mgL − 1 for Pb, Cd, Cr, Cu, Ni, and Mn respectively. Pb, Cd and Cr in water was found higher than TRV of US EPA. However, the HM content in the sediment, except for that of Cd, was greater than the standard values of TRV and TEL of US EPA, and limit of WHO/FAO. Pb and Cd were found at concentrations higher than the safe limits of the FAO in fishes. In fishes, the average HM concentrations decreased in the order Pb > Ni > Cu > Cd > Cr. In fish organs, HM concentration was estimated in the descending order of gut > gill > muscle. An ecological risk assessment revealed that sediment and water from the Pasur River suggested a moderate degree of pollution in water-based ecosystems. Bioaccumulation factor analysis indicated that accumulation of Cu, Ni, and Pb was relatively high in the fish gut. The higher TR values of Cd (3.72E- 04) and Ni (2.47E- 04) than the allowable level (TR > 10–04) indicated that consuming these fishes in large quantities over an extended period of time may result in carcinogenic health effects to humans.